An Analysis Of Recent Trends In Retail Sector In India (Trinity Journal of Management, IT & Media (TJMITM), 2012)
The Retail Sector of Indian Economy is going through the  phase of tremendous transformation. The retail sector of  Indian economy is categorized into two segments such as  organized retail sector and unorganized retail sector. In  Indian retailing sector the larger share of the retail market  is captured by unorganized sector. Currently, India is the  5th largest retail market in the world. The market size in  2010 was estimated at US$ 353 bn (Source: IBEF) and is  expected to reach US$ 543 bn by 2014. There are many  factors which are contributing the growth of retail sector  such as increase per capita income and living standard,  easy and low cost credit facilities, change in consumption  pattern, improvements in infrastructure, availability of retail  space and sources of financing. The proposed paper  would try to find out the factor, which are contributing in  growth of retail sector in India. We would also try to  compare the foreign and Indian retailing sector in terms of  total share of organized and unorganized retail sector,  Consumption spending and growth rate. The paper would  also try to explain current and future trends in retail sector  in India.
Keywords: Retail; Indian Economy; Organized Sector; Unorganized Sector; World Retail